Extraction on Display: Delving into Research, Curation, and Collaboration at a Liberal Arts College - Salas Landa, Mónica; Xu, Lijuan (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2024)
Drawing on our recent collaborative experience in teaching an intermediate-level museum studies course in Fall 2023, this reflective essay aims to demonstrate how faculty and librarians can employ object-centered research to guide students in their exploring and understanding of the extractive practices associated with imperialism and colonialism that have shaped museum and library collections. We specifically focus on the research and curatorial practices that culminated in an end-of-semester exhibit, showcased in both physical and digital formats. Through this exhibit, our student-curators brought to light the process of removing artifacts from their original material and political contexts and their subsequent integration into our collections. Moreover, they critically examined how classification and organization practices and, in certain instances, digitization processes in libraries, can either continue to veil or reveal the history of violence.